KEPEMIMPINAN KEPALA SEKOLAH DALAMMENINGKATKAN MUTU PENDIDIKAN - Achmad, Abdul Kholid (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
As an educational leadership, principals have a duty and responsibility which is quite heavy. Principals through their role and responsibilities to delegate it to aides and other parts. principal leadership in improving the quality of education include: instructive leadership style, leadership style consultative, participative leadership style, delegative leadership style and the quality of education through the process of determining the in-put and out-put processes (graduate). Efforts to improve the quality of school education is needed coaching to teachers and employees by the principal through (1) leadership style instructive addressed to teachers and employees who lacked the academic ability and spirit of performance is less, (2) a consultative leadership style in fostering the ability of teachers and employees of academic less and and the spirit of good works, (3) participative leadership style in fostering teachers and employees who have good academic ability and less fervor employees who have good academic ability, and excellent in performance.